2014
DOI: 10.1002/chem.201405792
|View full text |Cite
|
Sign up to set email alerts
|

Isosteric Substitutions of Urea to Thiourea and Selenourea in Aliphatic Oligourea Foldamers: Site‐Specific Perturbation of the Helix Geometry

Abstract: Nearly isosteric oxo to thioxo substitution was employed to interrogate the structure of foldamers with a urea backbone and explore the relationship between helical folding and hydrogen-bonding interactions. A series of oligomers with urea bonds substituted by thiourea bonds at discrete or all positions in the sequence have been prepared and their folding propensity was studied by using a combination of spectroscopic methods and X-ray diffraction. The outcome of oxo to thioxo replacements on the helical foldin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
45
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(51 citation statements)
references
References 91 publications
(30 reference statements)
6
45
0
Order By: Relevance
“…Both 5 and 6 show a strong band of positive ellipticity at 203 nm, and a secondary positive band at 218 nm. These bands result from homochromophoric or bichromophoric coupling of the π-π* thiourea transitions, 10 and are consistent with the adoption of a predominantly righthanded (P) helical screw sense. Because the helical oligomers are built from meso monomers, this preference for a right-handed screw sense can result only from the differentiated termini of the oligomer.…”
Section: Fig 1: Terminally-induced Control Of Hydrogen-bond Directiosupporting
confidence: 57%
“…Both 5 and 6 show a strong band of positive ellipticity at 203 nm, and a secondary positive band at 218 nm. These bands result from homochromophoric or bichromophoric coupling of the π-π* thiourea transitions, 10 and are consistent with the adoption of a predominantly righthanded (P) helical screw sense. Because the helical oligomers are built from meso monomers, this preference for a right-handed screw sense can result only from the differentiated termini of the oligomer.…”
Section: Fig 1: Terminally-induced Control Of Hydrogen-bond Directiosupporting
confidence: 57%
“…In line with this, Dado and Gellman elegantly used methionine side‐chain oxidation as a tool to fine‐tune polarity characteristics and were successful in identifying a redox‐switchable 18‐residue peptide 13. Studies on the effect of N‐terminal hydrophobicity on the α‐helix to β‐sheet transition in α‐peptides,14 redox‐switching of the Ac‐SIRKLEYEIEELRLRIG‐NH 2 peptide between extended and helical conformations by making use of its differential affinity towards Cu II /Cu I ions,15 photoswitching of peptide conformation with a built‐in azobenzene unit,16 chain‐length‐dependent 10‐ or 14‐helical preferences in trans ‐2‐aminocyclohexane carboxylic acid oligomer,17 solvent‐driven α‐ and 3 10 ‐helical preferences of an N ‐acylated homoheptapeptide isopropylamide based on L ‐α‐methylvaline in the crystalline state,18 partially unwound helical structure in hexameric oligourea containing a selenourea moiety proximate to the positive pole,19 partially unwound helical structure of a four residue γ‐peptide analogue having a carbamate–urea hybrid sequence,20 and zig‐zag tap‐like conformation stabilized by α‐ and γ‐turns in a hybrid octapeptide of leucine with a 8‐amino‐2‐quinolinecarboxylic acid derivative21 are some selected examples showing the active interest in understanding and manipulating folding preferences of peptides and peptide mimetics. Fülöp et al have previously shown that oligomers based on cis ‐2‐aminocyclopentanecarboxylic acid ( cis ‐ACPC) have a tendency to adopt an extended conformation, unlike their analogues based on trans ‐ACPC 22.…”
Section: Resultsmentioning
confidence: 99%
“…The oligomers were synthesized in solution using activated building blocks BB1 and BB2 as described previously ( Figure 2 and see general procedure for details). 8,33 Figure 2. Sequences of target (thio)urea-based hybrid oligomers 1-4 for investigating guanidinylation reaction in solution.…”
Section: Guanidinylation Reaction Of Urea/thiourea Hybrid Oligomers Imentioning
confidence: 99%
“…were synthesized in solution according to previously reported procedures. 6,8 for the cognate U 4 homooligourea foldamer. 7 Root-mean square deviations (RMSDs) calculated for the backbone asymmetric C atoms (CH(R)) of the two molecules highlights the correlation between the two structures (RMSD for residues 1-4 = 0.129 Å).…”
Section: Guanidinylation Of γ-Amino Acid-containing Oligo(thio)urea Smentioning
confidence: 99%